A new quantum evolutionary algorithm using dynamic rotation angle catastrophe for knapsack problem. (9th September 2019) - Li, Jialin; Li, Wei
In this paper, a quantum evolution algorithm (IQEA) based on dynamic rotation angle catastrophe technology is proposed to solve the knapsack problem. A quantum revolving gate operator with adaptive dynamic adjustment of the rotation angle is designed according to the evolution generations and fitness values. The population is divided into three parts equally, while preserving the optimal solution for each generation. Using the quantum rotation angles of different periods in the evolution process, the catastrophe operations of these three parts are carried out and the parallel evolution of four types of individuals is realised. With the guidance of better individuals, multi-path optimisation is performed to improve the parallelism of the algorithm. Effectively increase the diversity of the population, carry out multi-directional search and also retain the excellent information in the offspring population, ensuring the stability of the population. Experimental results show that the proposed algorithm is superior to traditional evolutionary algorithms and traditional quantum evolution algorithms.